ANALISIS PENGARUH JENIS SUBSTRAT TERHADAP KARAKTERISTIKANTENA MIKROSTRIP PERSEGI PANJANG DENGAN FREKUENSI KERJA 2,4 GHZ - Delva Zuletmei; Delsina Faiza; Khairi Budayawan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2017)
This research motivated by the influence kind of substrate to the dimensions of the antenna, gain and impedance, to get the design of antenna with the characteristic consistent with the standards and need of the designer takes the right material. This research to prove the effect of microstrip substrate. The substrate according to the design (features) and desirable for a rectangular microstrip antenna 2,4 GHz. Method used is analisis from the result of the simulation using CST studio suite, the process follow some steps: (1) study literature (2) determining the types antenna (3) determining the specifications of the microstrip antenna (2,4 GHz frequentz of resonance, return loss <-9,54 dB direction) (5) calculating the dimention of the antenna based on the theory (4) simulation using CST studio suite (5) analyzing the result of simulation. From the research can be concluded that there is a value £r of the gain the rectangular microstrip antenna where the larger value £r and the gain will be smaller. There is an influence in the value £r foward the bandwidth to the square antenna microstrip. Which is the more larger the value £r bandwidth make the value smaller. There is an influence in the value £r foward beamwidth to the square antenna mictrostrip, which is the more larger that value of £r, beamwidth will be larger. To design the antenna with high value more than 90° 5dB that is use for the value of £r between 1-3. To design the antenna with the beamwidth that value more than 0,03 GHz that use for the material with value of £r between 1-3.Keywords : kinds of substrate, gain, banwidth, beamwidth, antenna microstrip, CST studio suite